KNOWLEDGE, ATTITUDES, AND ASSOCIATED FACTORS REGARDING ORGAN AND TISSUE DONATION AMONG PHENIKAA UNIVERSITY STUDENTS IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: The study aims to describe the current knowledge and attitudes of students toward organ and tissue donation and transplantation, while also identifying key factors influencing these areas.Methods: A cross-sectional descriptive study was conducted with 384 students at Phenikaa University from January to May 2025.Results: Most students' knowledge scores regarding organ and tissue donation and transplantation were at an average level (58.1%), with only 2.3% achieving a high level of understanding. On a more positive note, a large majority of students (83.1%) expressed a favorable attitude toward donation. Notably, the "other gender" group showed the highest rate of positive attitudes at 90.0%. Statistical analysis revealed a significant correlation between a student's field of study and their attitude toward donation (p < 0.05). However, there were no significant differences found between general demographic characteristics and knowledge scores.Conclusion: These findings suggest that educational and communication programs should be specifically tailored to different target groups and academic contexts to maximize their effectiveness.
Keywords: Knowledge, attitude, students, organ donation, Phenikaa